2001
DOI: 10.1093/clinchem/47.11.2023
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease

Abstract: Background: Selective deamidation of glutamine residues by tissue transglutaminase (tTG) turns gliadin peptides into stronger activators of T cells from celiac disease (CD) patients. We examined the possibility that these modified peptides could be more specific epitopes for circulating antibodies than are native peptides. Methods: Two native synthetic peptides and their respective modified sequences were used as antigens for ELISA assays: peptide-1, with residues 56–75 of α-type gliadin; and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…It is intriguing to consider how antibodies to DGP could be specific to celiac disease. Two possible explanations have been offered as to why antibodies to deamidated gliadin epitopes exist in celiac patients, as cited by Aleanzi et al (16). Given that T cell reactivity is enhanced by deamidated (as opposed to native) gliadin sequences, B cell activation may be more robust to previously deamidated peptides.…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing to consider how antibodies to DGP could be specific to celiac disease. Two possible explanations have been offered as to why antibodies to deamidated gliadin epitopes exist in celiac patients, as cited by Aleanzi et al (16). Given that T cell reactivity is enhanced by deamidated (as opposed to native) gliadin sequences, B cell activation may be more robust to previously deamidated peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary gluten is partially digested into gliadin peptides that pass through the small bowel epithelium and are bound to the human leukocyte antigen HLA-DQ2 or DQ8 on the surface of antigen-presenting cells. This binding is strongly enhanced by deamidation, catalyzed by anti-tTG, thus resulting in a greatly enhanced T-cell (9,10) and antibody response (11). Recent studies have shown that deamidation increases binding of antibodies to gliadin in the sera of patients with CD but not of controls (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In several studies, selective deamidation of gliadin increased performance for both IgA and IgG in adult and pediatric patients with CD (11,12). In fact, the sensitivity and specificity of EIA using synthetic deamidated gliadin peptides (DGP) is considerably superior to whole gliadin (11,13). Studies have shown IgA anti-DGP to have up to 97% concordance with IgA anti-tTG and EMA with sensitivities exceeding 92% and specificities more than or equal to 99% (12,14,15).…”
mentioning
confidence: 99%
“…However, the reported sensitivity and specificity for IgA anti-AGA in CD vary widely (9). In several studies, selective deamidation of gliadin increased performance for both IgA and IgG in adult and pediatric patients with CD (11,12). In fact, the sensitivity and specificity of EIA using synthetic deamidated gliadin peptides (DGP) is considerably superior to whole gliadin (11,13).…”
mentioning
confidence: 99%